(untitled) (International Journal of Environmental Sciences, 2025)
Aim: To assess and compare the effect of different chelating agents on the push out bond strength of a three different root canal sealer to root dentin using Universal Testing Machine. Methodology: Ninety single-rooted teeth were randomly divided into 3 groups (n=30) and 3 sub-groups (n1, n2, n3=10) on basis of sealers and chelating agents respectively. Group I: [Bio-ceramic sealer]; Group II: [Resin-based sealer]; Group III: [Silicone-based sealer] divided in further sub-groups into A- 10% Citric acid (n1=10); B- 17% EDTA (n2=10); C- 7% Maleic acid (n3=10). NaOCl was used in irrigation procedures, and then the appropriate chelating agents were added. After preparation, canals were obturated with GP and respective sealers be it Bio-C sealer, Meta adseal plus and Guttaflow’2. A universal testing equipment was utilized to measure the strength of the push-out bond. Results: Intergroup comparison of POBS with 10% Citric Acid, 17% EDTA and 7% Maleic Acid resulted with Meta adseal plus exhibited highest bond strength followed by Bio-C sealer and lowest bond strength was conclusive with Guttaflow’2 (p = 0.001). Intragroup comparison of push out bond showed significant differences unlike in 10% Citric Acid Group II maintained uniform bond whereas Group I and Group III showed progressive increase in bond strength. Conclusion: Meta Adseal Plus showed the strongest adhesion in root canal sealing, penetrating deeper into the dentinal tubules. Bio-C sealer showed a moderate bond strength, while Guttaflow’2 showed the weakest adhesion, which made it less effective in preserving the long-lasting bonds within the root canal system.